Self-organized twist-heterostructures via aligned van der Waals epitaxy and solid-state transformations - Peter Sutter (Nature Portfolio, 2019)
Vertically stacked twisted layers of two-dimensional materials can trigger exciting fundamental physics. Here, authors report controlled growth of 30° twisted few-layer SnS2 over SnS2 via van der Waals epitaxy of an SnS intermediate and its transformation in the presence of excess sulfur.